POWER RELATIONS IN STUDENT-STUDENT INTERACTION: A PORTRAIT ON GENDER - Aldha Williyan; Aprilia Riyana Putri; Mochamad Guntur; Lili Sururi Asipi (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The students do not always feel at ease when working in groups or pairs. One of the reasons for this discomfort is the presence of power dynamics among the students. Therefore, this study focuses on investigating these dynamics and aims to achieve three main goals. Firstly, it aims to identify the indicators of power in student-student interactions between female and male EFL learners. Secondly, it aims to describe the relationships that are formed among them. Lastly, it aims to determine which participants exhibit more power in these interactions. The methodology employed in this study is qualitative, utilizing a classroom discourse analysis to identify the behaviors that manifest during student-student interactions. The data is examined using the theories of process types within systemic functional linguistics. The findings are then utilized to infer which participants wield more power in the interactions. The analysis reveals that a significant majority of the participants' process types indicate the presence of power. Furthermore, the relationship between female and male EFL learners is neither cooperative nor competitive, as one gender tends to dominate while the other has less ability to challenge this dominance. Thus, either female or male EFL learners can exhibit more power in the interaction. These findings indicate that power dynamics in interactions are not inherently tied to gender.